The effectiveness of location incentive: An analytical study of manufacturing SMEs in the Kedah State - Soo, Jan Jan; Golam Hassan, Asan Ali; Lim, Hock Eam (Universiti Utara Malaysia, 2009)
The main objective of this research is to find out the effectiveness of location incentive in att racting Small and Medium Enterprises (SMEs) to a certain industrial location in the state of Kedah. The location choice identified in this research would be Sungai Petani and non-Sungai Petani industrial areas. By using the logit model, we found that location incentive is not as effective as other factors in attracting SMEs in setting up their establishments in Kedah. The important factors that influence the location choice of manufacturing SMEs are (i) the years of operation of an SME, and (ii) the physical distribution of an SME product.